Clinical importance of p53 protein in gall bladder carcinoma and its precursor lesions. Issue 5 (May 1994) - Wee, A; Teh, M; Raju, G C
Abstract : AIMS–To study the expression and importance (if any) of p53 protein in gall bladder carcinoma and its precursor lesions. METHODS–Immunohistochemical staining was performed on formalin fixed, paraffin wax embedded histological sections with an anti-human p53 monoclonal antibody (DO-7; Dako Corporation M7001) (24 carcinomas, one adenocarcinoma in situ, six dysplasias, three adenomas and four cases of chronic cholecystitis). Invasive, in situ, and dysplastic areas as well as normal-looking epithelium were sought. Nuclear staining was assessed according to intensity and extent of positive cells. Both variables were graded on a scale of 1-3 and aggregate p53 scores were obtained (range: 0, 2-6). Only p53 scores of > or = 3 were regarded as significant. RESULTS–Clinically important amounts of p53 were expressed in 92% of invasive carcinomas, 86% of carcinoma in situ, and 28% of dysplastic areas. None of the adenomas contained clinically important amounts of p53. Normal epithelium, present in all the cases, did not express p53 except in one case of moderately differentiated adenocarcinoma (p53 score 3). In general, there was no difference in the prevalence of p53 protein expression between dysplasias associated with, and those unassociated with invasive disease. There was a tendency for higher grade carcinomas to express more p53 protein. CONCLUSIONS–The distribution of p53 protein in invasive carcinomas and the adjacent dysplastic and preinvasive lesions suggests that it is more commonly expressed than previously thought. The fact that p53 protein is also expressed in cases of dysplasia and carcinoma in situ unassociated with invasive malignancy lends further support to the contention that p53 gene mutations may have a role in the pathogenesis of gall bladder cancer. Expression of p53 protein may possibly be an indication of likely disease progression from dysplasia, to carcinoma in situ, to invasive disease.